Die belang van die interne publiek in openbare betrekkinge - Steenkamp Vorster (Communicare)
Should public relations officers tend to neglect the importance of their internal publics for the success of their organisations, the literature is explicit on the dangers of such negligence. In this article the nature of public relations as the important institutional communication function of organisations is explored with special reference to the importance of the attitudes and opinions of those who constitute an organisation's internal publics, as seen by various authors. The potential influence of employees, investors or other important groups as well as management itself on the public relations programme and the organisation itself is described and it is concluded that organisations with informed and motivating managements, devoted, motivated and loyal employees and supportive investors, will probably achieve greater overall success as those without these attributes. The public relations function should be encouraged by management to help achieve this through all the available communicative techniques.